Nationwide trends in the epidemiology of diabetic foot complications and lower-extremity amputation over an 8-year period. Issue 1 (11th October 2019) - Lin, Cheng-Wei; Armstrong, David G; Lin, Chia-Hung; Liu, Pi-Hua; Hung, Shih-Yuan; Lee, Shu-Ru; Huang, Chung-Huei; Huang, Yu-Yao
Abstract : Objective: To study the prevalence and trends of lower extremity complications of diabetes over an 8-year period in a single nation. Research design and methods: Nationwide data for people with type 2 diabetes (T2D) and diabetic foot complications (DFCs) were analyzed over an 8-year period (2007–2014) from National Health Insurance Research Database using the International Classification of Diseases, Ninth Revision disease coding. The DFCs were defined as ulcers, infections, gangrene, and hospitalization for peripheral arterial disease (PAD). Trends of patient characteristics, foot presentation, and the execution of major procedures were studied, including lower-extremity amputations (LEAs). Results: Along with the T2D population increasing over time, the absolute number of people with DFCs increased by 33.4%, but retained a prevalence of around 2% per year. The annual incident of LEAs decreased from 2.85 to 2.06 per 1000 T2D population (p=0.001) with the major LEA proportion decreasing from 56.2% to 47.4% (p<0.001). The mean age of patients increased from 65.3 to 66.3 years and most of the associated comorbidities of diabetes were increased. For example, end-stage renal disease increased from 4.9% to 7.7% (p=0.008). The incidence of gangrene on presentation decreased from 14.7% to 11.3% (p<0.001) with a concomitant increase in vascular interventions (6.2% to 19.5%, p<0.001). Conclusions: DFCs remain a sustained major medical problem. These nationwide long-term data suggest trends toward older people with greater comorbidities such as PAD and renal disease. Nevertheless, promising trends of reducing gangrene on presentation paired with increases in vascular interventions support continued vigilance and rapid, coordinated interdisciplinary diabetic foot care.